A clinical framework to facilitate selection of patients with differentiated thyroid cancer for active surveillance or less aggressive initial surgical management. Issue 2 (4th March 2018) - Tuttle, R. Michael; Zhang, Ling; Shaha, Ashok
ABSTRACT: Introduction : In the past, total thyroidectomy was usually recommended as the initial therapeutic approach in all but the lowest risk differentiated thyroid cancers. Today, many patients with low risk papillary thyroid cancers may be candidates for either an observational management approach (active surveillance/deferred surgical intervention) or a minimalist surgical approach (thyroid lobectomy/isthmusectomy). Areas covered : After a comprehensive review of the PubMed database and based on our clinical experience, we describe a clinical framework that integrates important factors in three major inter-related domains (pre-operative imaging/clinical findings, medical team characteristics, and patient characteristics) to classify a patient as either ideal, appropriate or inappropriate for conservative treatment options. As part of this clinical framework, we examine how the medical decision making construct (minimalist versus maximalist) of the patient and clinician can impact selection of initial therapy. Expert commentary : The dramatic rise in the incidence of very low risk differentiated thyroid cancer demands a re-evaluation of the appropriate use of more minimalistic treatment options. The selection of appropriate patients for less aggressive initial treatment options requires thoughtful, open discussions that can be aided by clinical decision making frameworks that recognize and value the medical decision making process of clinicians and patients.